2022
DOI: 10.1001/jama.2022.3337
|View full text |Cite|
|
Sign up to set email alerts
|

Aspirin Use to Prevent Cardiovascular Disease and Colorectal Cancer

Abstract: IMPORTANCE Low-dose aspirin is used for primary cardiovascular disease prevention and may have benefits for colorectal cancer prevention.OBJECTIVE To review the benefits and harms of aspirin in primary cardiovascular disease prevention and colorectal cancer prevention to inform the US Preventive Services Task Force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
96
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 120 publications
3
96
0
Order By: Relevance
“…55 For example, a recent trial in patients with familial adenomatous polyposis showed that aspirin significantly reduced incidence of recurrent polyp (aOR, 0.37), which may be relevant to colorectal cancer prevention. 26 56 Experimental studies have revealed various direct and indirect molecular targets of aspirin, affecting cellular proliferation, cell cycle, apoptosis, autophagy, lipid metabolism, and T cell function. 55 Among these pleiotropic effects, suppression of platelet-derived glycoprotein Ib-α by antiplatelet agents (aspirin, clopidogrel, and ticagrelor) but not by a nonaspirin nonsteroidal anti-inflammatory drug (NSAID) (sulindac) was shown to reduce HCC development in NAFLD HCC mouse model.…”
Section: Potential Hcc Chemoprevention Therapies With Generic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 For example, a recent trial in patients with familial adenomatous polyposis showed that aspirin significantly reduced incidence of recurrent polyp (aOR, 0.37), which may be relevant to colorectal cancer prevention. 26 56 Experimental studies have revealed various direct and indirect molecular targets of aspirin, affecting cellular proliferation, cell cycle, apoptosis, autophagy, lipid metabolism, and T cell function. 55 Among these pleiotropic effects, suppression of platelet-derived glycoprotein Ib-α by antiplatelet agents (aspirin, clopidogrel, and ticagrelor) but not by a nonaspirin nonsteroidal anti-inflammatory drug (NSAID) (sulindac) was shown to reduce HCC development in NAFLD HCC mouse model.…”
Section: Potential Hcc Chemoprevention Therapies With Generic Agentsmentioning
confidence: 99%
“…As a consequence, clinical trials to test candidate chemoprevention therapies are rarely successful despite the highly demanding and costly study design, which requires 1,000s to 10,000s subjects followed for nearly a decade. 25 26 In HCC, low-dose maintenance interferon was extensively evaluated in large multicenter prospective trials enrolling more than 1,000 patients with cirrhosis or advanced fibrosis in Europe and the United States, although the studies failed to demonstrate clinically meaningful chemopreventive effect. 27 28…”
Section: Challenges In Hcc Chemopreventionmentioning
confidence: 99%
“…Most other trials have not been powered for age-stratified analyses in women, and of the 13 trials analyzed in the 2022 USPSTF pooled analyses, 6 had prespecified subanalyses by sex and 3 trials were conducted only in men. 3…”
mentioning
confidence: 99%
“…The updated recommendations are based on pooled analyses of 13 randomized clinical trials for primary prevention, including a total of 161 680 participants without a history of ASCVD, of whom 53% were women . Low-dose aspirin (≤100 mg/d) was evaluated in 11 trials (N = 134 470 [63% women]) and was not associated with significant reduction in ASCVD mortality (odds ratio [OR], 0.95 [95% CI, 0.86-10.5]) or all-cause mortality (OR, 0.98 [95% CI, 0.93-1.03]).…”
mentioning
confidence: 99%
See 1 more Smart Citation